Pengaruh Kepemilikan Institusional, Ukuran Perusahaan dan Profitabilitas Terhadap Pengungkapan Corporate Social Responsibility - Fadli Rahmansyah; I Gusti Ketut Agung Ulupui; Ati Sumiati (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
Corporate Social Responsibility (CSR) is a concept that an organization, especially a company has a responsibility towards its stakeholders, namely consumers, employees, shareholders, communities and the environment in all aspects of the company’s operations. This research was conducted to determine the effect of institutional ownership, company size, and profitability on CSR disclosure. This research uses secondary data in the form of annual reports and sustainability reports of energy sector companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. Based on the test results, it showed that institutional ownership had no effect on CSR disclosure, firm size had a positive effect on CSR disclosure, and profitability had no effect on CSR disclosure. This study uses data for 2020 and 2021 where in that year there was an outbreak of SARS COVID-19 which was sweeping the world and affecting the world economy so that there were limitations in the data for that year. .